Novel PI3K/Akt Inhibitors Screened by the Cytoprotective Function of Human Immunodeficiency Virus Type 1 Tat - Kim, Yuri (Public Library of Science, 2011)
The PI3K/Akt pathway regulates various stress-related cellular responses such as cell survival, cell proliferation, metabolism and protein synthesis. Many cancer cell types display the activation of this pathway, and compounds inhibiting this cell survival pathway have been extensively evaluated as anti-cancer agents. In addition to cancers, several human viruses, such as HTLV, HPV, HCV and HIV-1, also modulate this pathway, presumably in order to extend the life span of the infected target cells for productive viral replication. The expression of HIV-1 Tat protein exhibited the cytoprotective effect in macrophages and a human microglial cell line by inhibiting the negative regulator of this pathway, PTEN. This cytoprotective effect of HIV-1 appears to contribute to the long-term survival and persistent HIV-1 production in human macrophage reservoirs. In this study we exploited the PI3K/Akt dependent cytoprotective effect of Tat-expressing CHME5 cells. We screened a collection of compounds known to modulate inflammation, and identified three novel compounds: Lancemaside A, Compound K and Arctigenin that abolished the cytoprotective phenotype of Tat-expressing CHME5 cells. All three compounds antagonized the kinase activity of Akt. Further detailed signaling studies revealed that each of these three compounds targeted different steps of the PI3K/Akt pathway. Arctigenin regulates the upstream PI3K enzyme from converting PIP2 to PIP3. Lancemaside A1 inhibited the movement of Akt to the plasma membrane, a critical step for Akt activation. Compound K inhibited Akt phosphorylation. This study supports that Tat-expressing CHME5 cells are an effective model system for screening novel PI3K/Akt inhibitors.